Fermented food packaging process: a case study of Khoriff by Bonda - Norhashimah, Maktar Zani; Fadzida, Ismail (Academia Industry Networks, 2022)
Packaging is to protect the product from damage that may occur during transportation, handling, and storage. It protects the product from moisture, light, heat, and other external factors. In addition, packaging methods also play an important role in describing the quality of the products produced. Product packaging process includes how the product is packaged and the characteristics of the materials used. This study is targeted on product packaging of fermented food (pekasam) by an enterprise named Khoriff by Bonda. The first purpose is to observe the current pekasam packaging process. Second, to investigate the challenges faced in pekasam packaging process. This study uses qualitative method in which data collection was conducted through interviews and observation. The results from the employees of the enterprise show that the process of pekasam packaging uses manual methods and the challenges of packaging the pekasam are the size of the raw materials, and the adoption of new technologies. With the proper use of automation, Khoriff by Bonda might be able to significantly increase the product productivity and profitability